Radioactive risk assessment of beach sand along the coastline of Mediterranean Sea at El-Arish area, North Sinai, Egypt. (April 2022) - Awad, M.; El Mezayen, A.M.; El Azab, A.; Alfi, S.M.; Ali, H.H.; Hanfi, M.Y.
Abstract: Beach sand includes various levels of natural radioactivity, which can cause health effects. The natural radioactivity was measured in the beach sand along the coastline of the Mediterranean Sea at the east of the El-Arish area, Egypt. Using the HPGe spectrometer, the contribution of radionuclides 226 Ra, 232 Th and 40 K in the gamma emitted radiation illustrated that the 226 Ra, 232 Th and 40 K activity concentrations are 8.8 ± 3.9, 30.8 ± 12.2 and 106.9 ± 46.8 Bq kg −1, respectively, which is lower than the reported worldwide limit 33, 45 and 412 Bq kg −1 . The radioactive hazards associated with the beach sand along the coastline of the Mediterranean Sea at the east of the El-Arish area were investigated. The obtained results among the radiological hazard parameters, the radium equivalent content (Raeq ), the absorbed dose rate (Dair ), annual effective dose (AED), external (Hex ) and internal (Hin ) hazard indices were estimated. Moreover, the excess lifetime cancer risk (ELCR) and the annual gonadal dose equivalent (AGDE) were also computed and illustrated their values less than the recommended levels. Multivariate statistical approaches like Pearson correlation, the principal component analysis (PCA) and the hierarchical cluster analysis (HCA) were applied to investigate the correlation between the radionuclides and the corresponding radiological hazard variables. Based on the statistical analysis, the 226 Ra and 232 Th mainly contribute to the radioactive risk of beach sand. Finally, no significant risk of the public associated with utilizing beach sand in building materials. Highlights: Beach sand includes various levels of natural radioactivity, which can cause health effects. Radiological hazard indexes were calculated and assessed the risk assessment. No significant natural radiation hazard comes from the beach sand in the studied area. The beach sand can be applied in different building materials.